2016
DOI: 10.1073/pnas.1601640113
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the mu opioid receptor gene in mice reshapes the reward–aversion connectome

Abstract: Connectome genetics seeks to uncover how genetic factors shape brain functional connectivity; however, the causal impact of a single gene's activity on whole-brain networks remains unknown. We tested whether the sole targeted deletion of the mu opioid receptor gene (Oprm1) alters the brain connectome in living mice. Hypothesis-free analysis of combined resting-state fMRI diffusion tractography showed pronounced modifications of functional connectivity with only minor changes in structural pathways. Fine-graine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 61 publications
5
63
0
Order By: Relevance
“…We further probed the status of whole-brain network activities in live animals, as previously done in (25). Resting-state functional Magnetic Resonance Imaging (Rs-fMRI) and the analysis of whole-brain connectivity (24) showed that the recruitment of DS, NAc and VTA as functional hubs differed in the brain of Dlx-MOR compared to Ctl mice (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further probed the status of whole-brain network activities in live animals, as previously done in (25). Resting-state functional Magnetic Resonance Imaging (Rs-fMRI) and the analysis of whole-brain connectivity (24) showed that the recruitment of DS, NAc and VTA as functional hubs differed in the brain of Dlx-MOR compared to Ctl mice (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Animal preparation, data acquisition and analysis were performed as described previously (24, 25), and directionality analysis conducted as described in Supplemental Information.…”
Section: Methodsmentioning
confidence: 99%
“…The μ receptor null mice thus reproduce the broadest autistic syndrome ever reported in preclinical research, proving unique face validity. Moreover, Oprm1 −/− mice display anatomical, neurochemical and genetic landmarks of the disease, such as modified neuronal activation in anxiety‐ and reward‐associated brain structures, reduced striatal connectivity, altered synaptic morphology and monoamine levels in the striatum and modified expression of several candidate genes of autism, providing construct validity to the model (Becker et al , ; Mechling et al , ). Finally, as regards predictive validity, risperidone and oxytocin, compounds that demonstrated efficiency in relieving autistic features in patients, also alleviated such symptoms in μ receptor null mice (Becker et al , ; Gigliucci et al , ).…”
Section: Genetic Manipulations Of the μ Opioid Receptor And Autistic‐mentioning
confidence: 99%
“…Since its onset in 2011 (Jonckers et al, 2011), mouse rsfMRI has developed in a number of centres and has grown to become a routine method with a number of applications, reviewed in (Chuang and Nasrallah, 2017;Gozzi and Schwarz, 2016;Hoyer et al, 2014;Jonckers et al, 2015Jonckers et al, , 2013Pan et al, 2015). Prominently, mouse rsfMRI has been used to investigate an extensive list of models, including Alzheimer's disease (Grandjean et al, 2014b, Shah et al, 2013, 2016cWiesmann et al, 2016;Zerbi et al, 2014), motor (DeSimone et al, 2016;Li et al, 2017), affective (Grandjean et al, 2016a), autism spectrum Haberl et al, 2015;Liska et al, 2018;Liska and Gozzi, 2016;Michetti et al, 2017;Sforazzini et al, 2016;Zerbi et al, 2018;Zhan et al, 2014), schizophrenia (Errico et al, 2015;Gass et al, 2016), pain (Buehlmann et al, 2018;Komaki et al, 2016), reward (Charbogne et al, 2017;Mechling et al, 2016), and demyelinating disorders (Hübner et al, 2017). Another application of mouse rsfMRI is the elucidation of large-scale functional alterations exerted by pharmacological agents (Razoux et al, 2013;Shah et al, 2016aShah et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%